Molecular Systematics of the Genus Hygrophila R.Br. (Acanthaceae) in India - Jaseela, V T (KSCSTE-Malabar Botanical Garden and Institute for Plant Sciences, Calicut. University of Calicut., 2024)
Hygrophila R.Br., a prominent genus within the tribe Ruellieae of the Acanthaceae family, is known for its diverse aquatic and semi-aquatic species, predominantly found in the Old-World tropics. Despite its ecological significance, the genus has been under-explored, particularly within India, where no comprehensive taxonomic studies have been conducted since the Flora of British India. This work addresses the taxonomic ambiguities and evolutionary relationships within the Indian species of Hygrophila through an integrative approach that combines morphological and molecular analyses. Consultation of major herbaria and literature survey recorded 15 species of Hygrophila in India. Extensive fieldwork across India facilitated the collection and identification of 12 Hygrophila species. The 3 species of Hygrophila (2 in Flora of British India and 1 from Little Andaman) were documented only once from their type localities and have not been reported since, making it impossible for us to collect them. Detailed descriptions, phenological data, distribution maps, and taxonomic keys for Indian Hygrophila species are provided. The research revealed a high species diversity in Peninsular India, with approximately 40% endemism. The study reported the extended distribution of Hygrophila phlomoides Nees from South India. Notably, the study reinstated Hygrophila phlomoides Nees and clarified the nomenclature and identity of several species. Morphological studies were complemented by molecular analyses using nuclear (ITS) and chloroplast (rbcL) genomes. This work represents the first molecular phylogenetic analysis of Hygrophila in India, contributing significantly to the global understanding of the genus. The phylogenetic data, supported by high bootstrap values, highlighted the non-monophyly of Hygrophila, suggesting the inclusion of the genus Brillantaisia P.Beauv. Based on this analysis, four species of Brillantaisia are proposed to be transferred to Hygrophila. These findings necessitate further global sampling to resolve taxonomic complexities within the genus. This comprehensive treatment of Hygrophila enhances the documentation of India's plant diversity and paves the way for future research in phytochemistry, pharmacology, and conservation. The study's outcomes, including submitting DNA sequences to GenBank and developing an optimized DNA extraction protocol, provide a foundation for subsequent systematic and evolutionary studies in Acanthaceae
Keywords: Hygrophila; Phylogeny; ITS; Taxonomy